(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Over the past 7 years, violent clashes in Cameroon between the military and armed separatists have driven thousands of Cameroonians to seek refuge in other parts of the country, and being known as Internally Displaced Persons (IDPs). All these displaced persons moved into other parts of Cameroon like Yaounde, Douala, Dschang and Baffousam, which are borders between Cameroon’s Anglophone and Francophone regions. The displaced, most of whom are women and children, face grave humanitarian issues that forces them to migrate to these areas. The print media estimates that over 246000 people have been internally displaced. Internally displaced persons abandon their homes, seeking shelter in nearby bushes and safe regions as a result of their entire communities set ablaze. Some of these vulnerable persons migrate to the French speaking regions for safety, education, employment and health aids. According to the research findings, about 68 per cent of IDPs are known to be women and children, with the elderly and disabled inclusive. Majority of the women have been abandoned by their husbands and as such they live in vulnerable conditions. Also, it shows that there have been gross impacts of war on the vulnerable that forces them into displacement. These are; loss of lives and property, educational barriers, poor health conditions and inability to access health facilities, separation from loved ones, trauma, poverty etc. Some of these turns our children into child hawkers, child bombers, exposure of females to sexual assaults and increase in loss of lives, just to name a few. The impacts mentioned above demands that the vulnerable be paid more attention to by the media and other concerned stakeholders, in order to remedy their challenges.